Moonday - Rex, Adam. (New York : Disney Hyperion Books, 2013)
When the Moon disrupts a town by lowering itself into someone's backyard, a child finds a way to return the Moon to its proper place in the sky.
Keywords: Moon -- Fiction; Imagination -- Juvenile fiction; Dreams -- Juvenile fiction; Moon -- Juvenile fiction